The contribution of sensory information asymmetry and bias of attribution to egocentric tendencies in effort comparison tasks - Stinson, Caedyn; Kagan, Igor; Pooresmaeili, Arezoo (Frontiers in Psychology, 2024)
When comparing themselves with others, people often evaluate their own behaviours more favourably. This egocentric tendency is often categorised as a bias of attribution, with favourable self-evaluation resulting from differing explanations of one's own behaviour and that of others. However, studies on information availability in social contexts offer an alternative explanation, ascribing egocentric biases to the inherent informational asymmetries between performing an action and merely observing it. Since biases of attribution and availability often co-exist and interact with each other, it is not known whether they are both necessary for the egocentric biases to emerge. In this study, we used a design that allowed us to directly compare the contribution of these two distinct sources of bias to judgements about the difficulty of an effortful task. Participants exhibited no attribution bias as judgements made for themselves did not differ from those made for others. Importantly, however, participants perceived the tasks they actively performed to be harder than the tasks they observed, and this bias was magnified as the overall task difficulty increased. These findings suggest that information asymmetries inherent to the difference between actively performing a task and observing it can drive egocentric biases in effort evaluations on their own and without a contribution from biases of attribution.